Projection and Social Responsibility in Law Schools - Ortiz Sanchez, Ivan (2010)
This paper is about the social projection and the university social responsibility along with the relationship that could have between the university and society, through the law schools. The author focuses in the university regulation, the university principles, as well as its aims in order to explain the relationship of the university and the society through the social projection that gives access to the social responsibility as an attitude that must promote and develop in its students. When discussing about the university social responsibility he indicates that it is based on the management approach that promotes the good practices in the internal administration and its engagement with society.  In addition, he refers that the university had promoted its own definition and theoretical model that constitutes a transversal approach with basic university functions, the social projection within them. The author refers that the USR model it been posited as one of mutual benefit between the university and the external actors.  In this line, he mentions that the university adopts a university social responsibility approach, but must not cancel the social projection in order to optimize the university work. Further on, the author indicates that the social projection/university social responsibility appears 21 years ago in the PUCP Law School with the Workshop. It operated with free legal clinics. In 1991, it institutionalizes the social projection in the Law School by the creation of the Law Social Projection programme, PROSODE. It had as a goal to promote the students integral learning and contribute to improve the living standard by offering free legal advices to the community.  It has different action areas: legal advice, legal education, legal diffusion and criminal-penitentiary. In addition, the author refers that there are other experiences in the Law School that tells us about the many actions of projection/social university responsibility that reinforce the relationship with society. Likewise, it been said that in Latin America there are many responsibility actions or social projection with various denominations, nature and methodology. Finally, the author indicates that there are many goals to the PUCP Law School in order to consolidate the social projection and the university social responsibility in the students teaching